Do Vertical Mergers Facilitate Upstream Collusion? - Nocke, Volker; White, Lucy (American Economic Review, 2007)
We investigate the impact of vertical mergers on upstream firms' ability to collude when selling to downstream firms in a repeated game. We show that vertical mergers give rise to an outlets effect: the deviation profits of cheating unintegrated firms are reduced as these firms can no longer profitably sell to the downstream affiliates of their integrated rivals. Vertical mergers also result in an opposing punishment effect: integrated firms typically make more profit in the punishment phase than unintegrated upstream firms. The net result of these effects in an unintegrated industry is to facilitate upstream collusion. We provide conditions under which further vertical integration also facilitates collusion. (JEL D43, G34, L12, L13)